The factors that influence online shopping intention among undergraduates in Malaysia case study of UiTM Puncak Alam, Selangor / Nur Alyaa Nasuha Abdul Ghani - Abdul Ghani, Nur Alyaa Nasuha (2015)
The main purpose of this study is to investigate the factors that can be considered as important factor of online shopping intention among undergraduates in Malaysia. Besides that, the objective of this study is to identify the most influential determinants of online shopping intention among undergraduates in Malaysia. The independent variables of this study are consisting of perceived usefulness, perceived ease of use and perceived enjoyment. There are one hundred and fifty (132) respondents from UiTM Puncak Alam, Selangor. This study used non-experimental research method which is descriptive research to find the relationship between dependent variable and independent variable. Other than that, primary data and secondary data also used to find information for supporting sampling technique. Furthermore, the researcher used questionnaire as the method to collect all the data from sample respondents in accomplishing the research objectives. The finding showed that perceived usefulness and perceived enjoyment has influence on online shopping intention among undergraduates in Malaysia. Therefore, the main factor that influences online shopping intention among undergraduates is perceived usefulness. The two variables which is perceived usefulness and perceived ease of use show positive relationship towards the online shopping intention among undergraduates.